Mussel inspired ZIF8 microcarriers: a new approach for large-scale production of stem cells. Issue 34 (27th May 2020) - Asadniaye Fardjahromi, Mahsa; Razmjou, Amir; Vesey, Graham; Ejeian, Fatemeh; Banerjee, Balarka; Chandra Mukhopadhyay, Subhas; Ebrahimi Warkiani, Majid
Abstract : Mussel inspired ZIF8 microcarriers with high surface area, biocompatibility, and nanoscale surface roughness are applied to enhance mesenchymal stem cell attachment and proliferation in 3D cell culture. Abstract : Metal–organic frameworks (MOFs) have high porosity, large surface area, and tunable functionality and have been widely used for drug loading. The aim of this study was to exploit unique features of zeolitic imidazolate framework-8 (ZIF8) to develop an innovative composite microcarrier (MC) for human mesenchymal stem cells (hMSCs) adhesion and proliferation. ZIF8 MCs were prepared by immobilization of polydopamine/polyethyleneimine (PDA/PEI) and ZIF8 on the surface of polystyrene beads. The chemical properties of MCs such as coating stability and homogeneity were characterized by different techniques such as ATR-FTIR, XRD, EDX, SEM, and contact angle. The prepared MCs were tested using human adipose-derived mesenchymal stem cells (hADSCs) in both static and dynamic conditions, and results were compared to a commercially available MC (Star-Plus), polydopamine coated MCs and amine-functionalized MCs as a control. Results show that PDA/PEI/ZIF8 coated MCs (in short: ZIF8 MCs) provides an excellent biocompatible environment for hADSCs adhesion and growth. In conclusion, ZIF8 MCs represent suitable and low-cost support for hADSCs culture and expansion, which can maximize cell yield and viability while preserving hADSCs multipotency. The present findings have revealed this strategy has the potential for chemical and topographical modification of MCs in tissue engineering applications.